G219(P) How do accidental mechanisms of childhood injury relate to the pattern of bruising seen on examination?. (27th April 2016) - Hibberd, O; Nuttall, D; Watson, R; Kemp, AM; Maguire, S
Abstract : Aim: To inform an evidence-based assessment of the plausibility of proposed mechanisms of bruising in children. Methods: A prospective cross sectional study of children 0–13 years (mean 68.5 months, SD 39) attending the Emergency Department (ED), and children in the local community. 50.2% of the ED cohort were attending ED for a reason other than the injury causing the bruise. The community cohort were aged 0–6 years (mean 26.87 months, SD 15). Children were eligible for inclusion if they had a bruise of known origin; excluded if they had a known bleeding disorder, were receiving medication that might impair coagulation or had any child protection concerns. Injuries were categorised as one of eight mechanisms (fall from; < 1metre, 1–2 metres, from standing hitting an object, stairs, impact, crush, sports or Motor Vehicle Collision (MVC)). The location and number of bruises per injury episode were recorded (by parents in the community cohort, and by researcher in ED). The presence of petechial bruising was recorded for the ED cohort only. Results: 373 children had 560 injury episodes resulting in 694 bruises. Across all mechanisms, 81.8% of incidents resulted in a single bruise, the exceptions being sports injuries, stair falls and MVC. Most frequent mechanisms were falls from < 1 metre and impact injuries, with commonest sites of bruising for all mechanisms being shins and forehead. The only mechanisms accounting for simultaneous bruises to the front and back of body were a stair fall from 12 steps and a MVC. Of 25 stair falls, only those falling > 10 steps had ≥3 bruises (6 cases). Regardless of mechanism, certain sites had no bruises in this dataset, namely ears, neck and genitalia (Table). Petechial bruising was only observed in 1/293 episodes, from a high impact injury in a school aged child. Conclusion: This study provides novel data recording patterns of bruising from specific injury mechanisms, to aid clinicians in determining the plausibility of the history offered relative to bruising seen. Certain patterns were rarely observed, namely multiple bruises from a single mechanism, petechial bruising, and bruising to the ears, neck or genitalia.